2017
DOI: 10.3389/fpsyg.2017.00884
|View full text |Cite
|
Sign up to set email alerts
|

Barking up the Wrong Tree: Why and How We May Need to Revise Alcohol Addiction Therapy

Abstract: One of the main characteristics of alcohol abuse and addiction is the loss of control over alcohol intake and the continuation of drinking in the face of negative consequences. Mounting evidence strongly suggests that an alcohol-induced imbalance between goal-directed and habitual behavior may be one of the main driving factors of this key feature of addiction and furthermore play a key role in staying abstinent. Current therapies often focus only on deficient inhibitory control (i.e., goal-directed behavior),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Several reviews and meta-analyses have covered literature on one or more of the three aforementioned alcohol-related CBMs, with some of them reaching a rather positive conclusion (17,18), while others were more cautious (19)(20)(21)(22). Most authors agreed that future studies should expand research to clinical samples, clarify which cognitive construct is best targeted, and enlarge knowledge about the moderating factors and mechanisms of action (17,20,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews and meta-analyses have covered literature on one or more of the three aforementioned alcohol-related CBMs, with some of them reaching a rather positive conclusion (17,18), while others were more cautious (19)(20)(21)(22). Most authors agreed that future studies should expand research to clinical samples, clarify which cognitive construct is best targeted, and enlarge knowledge about the moderating factors and mechanisms of action (17,20,23).…”
Section: Introductionmentioning
confidence: 99%
“…Acute alcohol intoxication and alcohol use disorder (AUD) strongly impair executive functions [2]. These impairments may contribute to maladaptive and dysfunctional behavior [3] that affects different aspects of life, including occupation [4].…”
Section: Introductionmentioning
confidence: 99%
“…While it is still unclear whether or how these two consequences are functionally linked, it has been shown that the acute cognitive effects of a high-dose alcohol intoxication resemble the pattern of cognitive deficits observed in AUD patients—both produce pronounced impairments in cognitive control/executive functioning, while behavioural automaticity is comparatively preserved [16,17,18,19,20]. This imbalance between behavioural control and automaticity has repeatedly been shown to play an important role in the development and maintenance of AUD [21] but it has never been investigated whether such specific effects can also be found during alcohol hangover (which should be a regular occurrence in frequent binge drinkers). Demonstrating the persistence of such detrimental effects during hangover (i.e., beyond acute intoxication) would provide an important functional link, which may help to explain why and how regular binge drinking increases the risk of developing AUD [13,14,15]: If impairments of cognitive control functions persisted beyond acute intoxication, the poor cognitive functioning on the day following alcohol use might promote continued aberrant drinking as well as other decisions that may be detrimental to the overall health of affected individuals.…”
Section: Introductionmentioning
confidence: 99%